Frequent cases of RAS-mutated down syndrome acute lymphoblastic leukaemia lack JAK2 mutations - Nikolaev, Sergey I. (2014)
Children with Down syndrome (DS) and acute lymphoblastic leukaemia (ALL) have poorer survival and more relapses than non-DS children with ALL, highlighting an urgent need for deeper mechanistic understanding of DS–ALL. Here, using full-exome or cancer genes-targeted sequencing of 42 ALL samples from 39 DS patients, we uncover driver mutations in RAS, (​KRAS and ​NRAS) recurring to a similar extent (15/42) as ​JAK2 (12/42) mutations or ​P2RY8-​CRLF2 fusions (14/42). RAS mutations are almost completely mutually exclusive with ​JAK2 mutations (P=0.016), driving a combined total of two-thirds of analysed cases. Clonal architecture analysis reveals that both RAS and ​JAK2 drove sub-clonal expansions primarily initiated by ​CRLF2 rearrangements, and/or mutations in chromatin remodellers and lymphocyte differentiation factors. Remarkably, in 2/3 relapsed cases, there is a switch from a primary ​JAK2- or ​PTPN11-mutated sub-clone to a RAS-mutated sub-clone in relapse. These results provide important new insights informing the patient stratification strategies for targeted therapeutic approaches for DS–ALL.